Anak Mengalami Kebutaan Akibat Kekerasan Fisik: Apa Hukumnya? - Amara, Nouna Shaina; Zubaedah, Rahmi (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Cases of physical violence committed by minors continue to occur and increase in Indonesia. One of them was a case of physical violence that befell an elementary school student in Gresik which resulted in permanent blindness due to a meatball stab attack by her senior in one eye. This research is intended to find out about legal protection for minor victims who experience physical violence and how the law in Indonesia regulates the justice of minors who commit criminal acts. By using normative juridical research methods and using secondary data in the form of articles, published news and previous research and using positive law in Indonesia, namely, Law Number 23 of 2002 concerning Child Protection, Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. It is hoped that this research will provide comprehensive insight regarding law enforcement efforts and the protection of minors in Indonesia.